Pencegahan Covid-19 Pada Pemuda GBIS Kristus Pengharapan Medan - Novita Hasiani Simanjuntak (LPPM Universitas HKBP Nommensen, 2021)
Covid-19 is still a pandemic, and showing an increase globally. Government policies are needed to assist youth in coping with this disaster by implementing effective measures. Thus, counseling is needed for youth to increase knowledge, know how to protect oneself, protect themselves and others in order to achieve preparedness against this disaster. This Community Service in the form of an outreach entitled